Evaluation of Commercially Available Fall Detection Systems - Hrubý, Dan; Černý, Martin (Studies in health technology and informatics, 2023)
Falls are a serious problem in the hospital setting and home environments. However, this problem does not only affect the elderly, but also people who have had surgery, have disabling problems, have associated diagnoses (such as poor eyesight, confusion, etc.) or are dizzy or have walking aids. The aim of research was to find, compare and implement fall detectors especially for the hospital environment. This paper summarizes possible fall detectors. Various technological solutions were selected for testing, including wearable technologies as well as contactless technologies based on PIR detectors and mmWave technologies. The selected fall detectors were tested in living laboratory of HEALTHLab.vsb.cz and then in Hospital AGEL Třinec - Podlesí. The best result of the testing was the use of two Vayyar Home Care devices in one room, thus achieving a detection accuracy of 92.50 % and a sensitivity of 92.50 %.
Keywords: závrať; Hospitals; služby domácí péče; Accidental Falls; Dizziness; laboratoře; Home Care Services; Laboratories; Aged; lidé; senioři; nemocnice; Humans; úrazy pádem